Effect Comparison of Moringa oleifera L. Extract Supplementation to Cauda Epididymis Plasma Diluent on Simmental Semen - Aldinsyah, Arsya Aufiyyah; Ducha, Nur; Fitriana, Dhanis (Fakultas Peternakan, Universitas Padjadjaran, 2026)
The success of Artificial Insemination (AI) programs in cattle largely depends on the quality of semen after freezing. This study aimed to evaluate the effect of supplementing cauda epididymis plasma (CEP) diluent by Moringa oleifera seed extract (MSE) on the post-thaw quality of Simmental bull semen. Semen samples were collected by bulls by individual motility ≥70% and processed at the Singosari Artificial Insemination Center between October and December 2024. The study employed a Completely Randomized Design (CRD) by four MSE concentrations: 0, 1, 5, and 10 mg/mL of MSE. each tested replicated in six for motility, viability, and membrane integrity. Observations were conducted utilizing microscopy and evaluated statistically by ANOVA and Duncan’s test. The outcomings indicated that 5 mg/mL of MSE yielded the highest semen quality post-thaw, by motility of 43.33±3.73%, viability of 83.17±1.07%, and membrane integrity of 84.08±1.06% (P<0.05). These outcome demonstrate that MSE supplementation enhances the antioxidant capacity of the CEP diluent, effectively reducing oxidative damage and preserving semen quality during cryopreservation. This suggests that Moringa oleifera seed extract represents a promising natural additive for improving the efficacy of frozen semen used in artificial insemination programs.